Solvent-induced surface disorder and doping-induced lattice distortion in anatase TiO2 nanocrystals for enhanced photoreversible color switching. Issue 8 (31st January 2019) - Yang, Kewei; Chen, Xiaoyu; Zheng, Zhenhuan; Wan, Jiaqi; Feng, Miao; Yu, Yan
Abstract : Photoreversible color switching based on anatase TiO2 nanocrystals was regulated by solvent-induced surface disorder and Sn 2+ doping-induced lattice distortion. Abstract : TiO2 nanocrystal (NC)-based photoreversible color switching (PCS) materials, which are capable of actively responding to external light, have significant potential for use in printable rewritable paper in the creation of sustainable technologies. Reductive TiO2 NCs with high hole-scavenging capabilities can be obtained by surface disorder or lattice distortion, but achieving an optimum balance between them is still a great challenge to enable simultaneous retention of the photoreduction performance and visible light catalytic ability of the TiO2 NCs. Here, we demonstrated solvent-controlled synthesis of interstitial Sn 2+ -doped TiO2 NCs and investigated the effects of solvent-induced surface disorder and doping-induced lattice distortion on the PCS properties of the TiO2 NCs. The midgap state produced by surface disorder combines with the energy level produced by the interstitial Sn 2+ dopants in TiO2 NCs to become the main center for photogenerated electron transfer. Thus, efficient PCS was achieved, with the number of switching cycles greatly increased. The ethylene glycol-synthesized TiO2 NCs with a Sn 2+ -doping concentration of ca. 3% are the most favorable catalyst for achieving PCS performance. The process of PCS can be repeated 48 times without any rest. The results of this work suggest an approach to the design and preparation of PCS materials that exhibit excellent scalability and outstanding reversible performance by using colloidal NCs with optimized surface composition, lattice structure, and particle size as key-functional photocatalysts.